2011
DOI: 10.1021/jm201231w
|View full text |Cite
|
Sign up to set email alerts
|

(1S, 3S)-3-Amino-4-difluoromethylenyl-1-cyclopentanoic Acid (CPP-115), a Potent γ-Aminobutyric Acid Aminotransferase Inactivator for the Treatment of Cocaine Addiction

Abstract: Vigabatrin, a GABA aminotransferase (GABA-AT) inactivator, is used to treat infantile spasms and refractory complex partial seizures and is in clinical trials to treat addiction. We evaluated a novel GABA-AT inactivator (CPP-115) and observed that it does not exhibit other GABAergic or off-target activities and is rapidly and completely orally absorbed and eliminated. Using in vivo microdialysis techniques in freely moving rats and micro-PET imaging techniques, CPP-115 produced similar inhibition of cocaine-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 46 publications
1
68
0
Order By: Relevance
“…Carisbamate has since been granted orphan drug status for IS by the Food and Drug Administration (FDA). Another promising drug is CPP-115, a vigabatrin analog with high affinity for GABA aminotransferase that has shown lower retinal toxicity than vigabatrin (Pan et al 2012; Silverman 2012). CPP-115 reduced spasms in the multiple-hit model showing better efficacy / tolerability profile than vigabatrin, at doses 400 times lower than vigabatrin (Briggs et al 2014).…”
Section: West Syndrome and Infantile Spasmsmentioning
confidence: 99%
“…Carisbamate has since been granted orphan drug status for IS by the Food and Drug Administration (FDA). Another promising drug is CPP-115, a vigabatrin analog with high affinity for GABA aminotransferase that has shown lower retinal toxicity than vigabatrin (Pan et al 2012; Silverman 2012). CPP-115 reduced spasms in the multiple-hit model showing better efficacy / tolerability profile than vigabatrin, at doses 400 times lower than vigabatrin (Briggs et al 2014).…”
Section: West Syndrome and Infantile Spasmsmentioning
confidence: 99%
“…[intraperitoneally], PN4 -13), but transiently respond to vigabatrin (Scantlebury et al 2010), whereas, appropriately for IS, do not respond to phenytoin (Table 4) . Further confirming the responsiveness to vigabatrin, a recently developed high-affinity inactivator of GABA aminotransferase, CPP-115 (Catalyst Pharmaceutical Partners, Coral Gables, FL), which shows lower than vigabatrin risk for retinal toxicity in animal studies (Pan et al 2012;Silverman 2012), showed better efficacy/tolerability profile in the multiple-hit model (Briggs et al 2014).…”
Section: Animal Models Of Early-life Epilepsymentioning
confidence: 87%
“…A novel GABA-AT inhibitor with increased effectiveness at lower doses and greater target specificity, CPP-115 displays superior enzyme inactivation in comparison to GVG [115]. This medication is currently under Phase II investigation for treatment of cocaine use disorders.…”
Section: Vigabatrin and Its Analoguesmentioning
confidence: 99%